2019
DOI: 10.1111/vde.12821
|View full text |Cite
|
Sign up to set email alerts
|

A small scale study to evaluate the efficacy of microneedling in the presence or absence of platelet‐rich plasma in the treatment of post‐clipping alopecia in dogs

Abstract: Background -Post-clipping alopecia often has a clinically poor response to therapy and prolonged alopecia is a source of anxiety for some owners. In humans and dogs, superficial microtrauma via a microneedling (MN) device induces mechanical stimulation of the hair follicle with resultant hair regrowth. Human studies suggest that concurrent application of platelet-rich plasma (PRP) with MN induces more rapid regrowth of better-quality hair than microneedling alone.Hypothesis -Microneedling with PRP will induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…One report revealed that certain body sites, such as the hind legs, rump and tail, were less responsive to MN in dogs, while another report did not. 4,13 In this study, we assumed that certain body sites were less responsive to MN because the device could not be firmly applied to the uneven surface. Therefore, the dorsum was selected for our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One report revealed that certain body sites, such as the hind legs, rump and tail, were less responsive to MN in dogs, while another report did not. 4,13 In this study, we assumed that certain body sites were less responsive to MN because the device could not be firmly applied to the uneven surface. Therefore, the dorsum was selected for our study.…”
Section: Discussionmentioning
confidence: 99%
“…Yeong-Hun Kang 1 | Min-Sun Kim 1 | Soh-Yoon Kang and permanent hair regrowth with negligible adverse effects. 4,13 In mice, 0.25 and 0.5 mm needles produced significantly more hair growth than other needle lengths. 19 In dogs, the reported lengths of needles were 1.5 and 2.5 mm.…”
Section: Optimal Microneedle Length For Hair Regrowth In Hair Cycle A...mentioning
confidence: 97%
See 2 more Smart Citations
“…In recent years, multiple effects of PRP have been documented in vivo and in vitro in human and veterinary medicine. In dogs, clinical studies are focused on orthopedics uses [35][36][37][38][39] and in dermatology for the treatment of wounds [40] or skin ulcers with extensive tissue loss [41][42][43], chronic ulcers [44], surgically induced wounds [45][46][47][48], alopecia [49] and for antimicrobial effects in infected skin wounds [50]. The results of these studies have been variable which may reflect the lack of standardization of the methods for obtaining the PRP.…”
Section: Of 16mentioning
confidence: 99%